Annual Plan 2010-11 Govt. of NCT of Delhi - Planning Commission (Planning Commission, 2010)
Annual Plan 2010-11 of Delhi has been prepared within the broad framework and approved by the Government for the 11th Five Year Plan (2007-2012) of Delhi in the form of Approach Paper titled "Development Plan a human face and making Delhi a Global City" in September 2006.
Govt. of NCT of Delhi, Planning Department